Parent‐adolescent conflict processes and their measurement: A systematic review. Issue 1 (19th October 2022) - Marshall, Sheila K.; Tilton‐Weaver, Lauree; Shankar, Sneha; Johnston, Andrea
Abstract: Conflicts are frequently incorporated into research on parent‐adolescent relationships. However, empirical research has inconsistently used "parent‐adolescent conflict" as a broad and often singular term rather than processes involving a range of constructs. To understand the balance of attention to the constructs involved in parent‐adolescent conflicts, we conducted a systematic review of measures that were reported in peer‐reviewed journal articles between January 1, 1970 and January 31, 2021, across several disciplines. The initial search identified 17, 036 references; after removing duplicates, excluding studies based on stated criteria, and adding 22 articles from reference lists, 467 articles were retained, and 568 measures were extracted from articles. Two types of content analysis (directed and conventional) were used to organize measures into categories. Findings reveal that conflict frequency, intensity, and quality of interactions are most often used while initiation and duration tend to be overlooked. Uneven coverage may generate biases in understanding parent‐adolescent conflict processes.